Manufacturing method of multi-angle wedge-shaped PVB (polyvinyl butyral) intermediate film

By adding compound modified base liquid and using high-efficiency extruders and high-precision wedge-shaped molds in the production process of PVB interlayer films, the problem of insufficient high-temperature fluidity of PVB interlayer films was solved, and precise multi-angle wedge-shaped structures and clear The image display improves driving safety.

CN119348095AInactive Publication Date: 2025-01-24YINIAN OPTICS (SUZHOU) CO LTD

Patent Information

Application Number
CN202411493100.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing PVB intermediate film lacks fluidity at high temperatures, resulting in the wedge structure being unable to be accurately controlled, and image ghosting occurs, affecting driving safety.

Method used

By adding a compound modified base fluid, including new ester oil and new compound silane coupling agent, in the production process of the PVB interlayer film, the high-temperature fluidity is improved, and it is formed through a high-efficiency extruder and a high-precision wedge mold. Control the wedge degree at 0.2-0.8mrad.

Benefits of technology

The accurate multi -angle wedge structure of the PVB intermediate membrane is implemented, which significantly reduces the image of the image, and ensures that the driver sees a clear and heavy shadow projection image, which improves driving safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005100589830000081
    Figure BDA0005100589830000081
  • Figure BDA0005100589830000091
    Figure BDA0005100589830000091
Patent Text Reader

Abstract

The invention discloses a manufacturing method of a multi-angle wedge-shaped PVB (polyvinyl butyral) intermediate film, and relates to the technical field of PVB intermediate films, the manufacturing method comprises the following steps: step 1, preparing a mixture of PVB resin and a plasticizer; 2, synthesizing a compound modified basic solution; step 3, adding the compound modified basic solution into the PVB mixture; step 4, carrying out extrusion molding through an efficient extruder, wherein the extrusion temperature is controlled to be 120-160 DEG C; a high-precision wedge-shaped mold is used for forming, and the wedge-shaped degree is controlled to be 0.2 mrad to 0.8 mrad; and an efficient cooling system is adopted for cooling and curing. By adding the compound modified basic solution, the high-temperature fluidity and mechanical properties of the PVB intermediate film are improved, so that the light transmittance, haze, binding power and penetration resistance are ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a PVB intermediate film, and more specifically to a method for manufacturing a multi-angle wedge-shaped PVB intermediate film. Background Art

[0002] In modern cars, head-up displays (HUD) and advanced driver assistance systems (ADAS) have become important components for improving driving safety and comfort. HUD can project key data such as navigation information and driving speed directly into the driver's field of view, so that the driver does not need to look down at the dashboard, thereby improving driving safety. The ADAS system monitors the vehicle's surroundings in real time through sensors such as cameras and radars, and provides functions such as early warning, lane keeping, and automatic emergency braking, further improving driving safety.

[0003] PVB interlayer is required in head-up displays (HUD) and advanced driver assistance systems (ADAS), and is used in automotive laminated glass to improve the safety and optical properties of the glass. However, during the production process of existing PVB interlayers, due to insufficient high-temperature fluidity, the wedge-shaped structure produced cannot be precisely controlled. As a result, when the laminated glass is used in the system, image ghosting is prone to occur in extreme environments, affecting driving safety.

[0004] Therefore, a new solution needs to be proposed to solve this problem. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a method for manufacturing a multi-angle wedge-shaped PVB interlayer.

[0006] The technical solution of the present invention is:

[0007] A method for manufacturing a multi-angle wedge-shaped PVB interlayer comprises the following steps

[0008] Step 1, preparing a mixture of PVB resin and plasticizer;

[0009] Step 2, synthesizing a composite modified base liquid;

[0010] Step 3, adding the compounded modified base liquid to the PVB mixture;

[0011] Step 4: Extrusion molding is performed using a high-efficiency extruder, and the extrusion temperature is controlled at 120-160°C; molding is performed using a high-precision wedge-shaped mold, and the wedge degree is controlled at 0.2-0.8mrad; and cooling and solidification are performed using an efficient cooling system.

[0012] The present invention is further configured such that the compound modified base liquid comprises a novel ester oil and a composite novel silane coupling agent.

[0013] The present invention is further configured such that the proportion of the composite novel silane coupling agent in the composite modified base liquid is in the range of 2-5%, and the rest is the novel ester oil.

[0014] The present invention is further configured that the novel ester oil is synthesized by esterification reaction of glycerol and adipic acid under the action of p-toluenesulfonic acid catalyst.

[0015] The present invention is further configured that the novel composite silane coupling agent is synthesized by trichlorosilane and triethoxysilane under the action of a platinum catalyst.

[0016] The present invention is further configured such that, in the mixture of the PVB resin and the plasticizer, the proportion of the PVB resin is 78-80%, and the proportion of the plasticizer is 17-19%.

[0017] The present invention is further configured such that the novel ester oil and the novel composite silane coupling agent are both neutralized by sodium hydroxide solution and refined by reduced pressure distillation.

[0018] The beneficial technical effects of the present invention are:

[0019] The invention improves the high-temperature fluidity of the PVB interlayer by adding a compound modified base liquid during the production process of the PVB interlayer, so that the PVB interlayer can flow and fill more evenly in the mold, thereby realizing a precise multi-angle wedge structure and controlling the wedge degree to be 0.2-0.8 mrad, significantly reducing the image ghosting phenomenon, and ensuring that the driver always sees a clear, ghost-free projection image. DETAILED DESCRIPTION

[0020] In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the specific implementation methods of the present invention are further described in detail below in conjunction with specific embodiments. The following embodiments are used to illustrate the present invention but are not used to limit the scope of the present invention.

[0021] Embodiment 1, a method for manufacturing a multi-angle wedge-shaped PVB interlayer, comprising the following steps:

[0022] Step 1, preparing a mixture of PVB resin and plasticizer, weighing 78% of PVB resin and 17% of triethylene glycol diisooctanoate, mixing the two and stirring them evenly to obtain a mixture;

[0023] Step 2: synthesize the composite modified base liquid, weigh a certain amount of glycerol and adipic acid, mix them in a molar ratio of 1:1, add 0.5% p-toluenesulfonic acid catalyst into the reactor, control the temperature at 140°C for esterification reaction, and the reaction time is 4 hours. The esterification reaction equation is as follows:

[0024] C3H8O3+C6H 10 O4→Ci2H 22 O6+2H2O

[0025] Among them, C3H8O3 is glycerol, C6H 10 O4 is adipic acid, and the product is a new type of ester oil Ci2H 22 O6 and water, after the reaction is completed, 10% sodium hydroxide solution is added for neutralization, and finally a high-purity new ester oil is obtained by vacuum distillation;

[0026] Weigh a certain amount of trichlorosilane and triethoxysilane, mix them in a molar ratio of 1:1.1, add 0.1% of platinum catalyst in the reactor, control the temperature at 90°C for reaction, and the reaction time is 3 hours. The reaction equation is as follows:

[0027] SiCl3H+Si(OC2H5)3→SiCl3Si(OC2H5)3

[0028] Among them, SiCl3H is trichlorosilane, Si(OC2H5)3 is triethoxysilane, and the product is a composite new silane coupling agent SiCl3Si(OC2H5)3;

[0029] After the reaction is completed, 10% sodium hydroxide solution is added for neutralization, and finally a high-purity composite novel silane coupling agent is obtained by reduced pressure distillation.

[0030] Step 3: Weigh the prepared new ester oil and the composite new silane coupling agent at a ratio of 3%, add them to the mixture of PVB resin and plasticizer, and weigh 1% of the adhesion regulator, add them to the mixture, stir evenly, and mix thoroughly. The mixing time is 45 minutes, and the mixing temperature is controlled at 50° C. to ensure that the components are evenly distributed;

[0031] Step 4: Extrusion the mixed raw materials through an extruder. The extrusion temperature is controlled at 140°C and the extrusion volume is controlled at 1500kg / h. During the extrusion process, the temperature and pressure are monitored in real time to ensure that the materials are evenly melted and extruded smoothly. The speed of the extruder screw is controlled at 60rpm to ensure that the materials are fully mixed and evenly extruded;

[0032] A high-precision wedge-shaped mold is selected, and the inner surface of the mold is polished to ensure its smoothness and dimensional accuracy. The extruded PVB molten material is formed through the mold. The mold temperature is controlled at 200°C. The temperature is adjusted according to the change in the thickness of the diaphragm. The temperature is higher in the thick part to ensure fluidity. By precisely controlling the temperature and pressure inside the mold, a multi-angle wedge structure is formed. The wedge degree range is controlled at 0.4-0.6mrad to ensure that the thickness and angle of different areas meet the design requirements;

[0033] Use efficient cooling devices, a combination of air cooling and water cooling, to quickly reduce the temperature of the diaphragm. The cooling speed is controlled within a moderate range to prevent internal stress and deformation caused by too fast or too slow cooling, ensuring the dimensional stability and uniform internal structure of the diaphragm. During the curing process, the temperature is controlled at room temperature to ensure the ultimate performance of the diaphragm.

[0034] The difference between Example 2 and Example 1 is that the ratio of silane coupling agent and new ester oil in the compound modified base liquid is adjusted to 3.5%, the extrusion temperature is 145°C, the extrusion volume is 1600kg / h, and the mold temperature is 210°C.

[0035] The difference between Example 3 and Example 1 is that the ratio of silane coupling agent and new ester oil in the compound modified base liquid is adjusted to 2.5%, the extrusion temperature is 135°C, the extrusion volume is 1400kg / h, and the mold temperature is 190°C.

[0036] The fourth embodiment is different from the first embodiment in that the ratio of the silane coupling agent and the new ester oil in the compound modified base liquid is adjusted to 4%, the extrusion temperature is 150°C, the extrusion volume is 1700kg / h, and the mold temperature is 220°C.

[0037] Example 5 is different from Example 1 in that the ratio of the silane coupling agent and the new ester oil in the compound modified base liquid is adjusted to 2%, the extrusion temperature is 130°C, the extrusion volume is 1300kg / h, and the mold temperature is 180°C.

[0038] Example 6 is different from Example 1 in that the ratio of silane coupling agent and new ester oil in the compound modified base liquid is adjusted to 5%, the extrusion temperature is 155°C, the extrusion volume is 1800kg / h, and the mold temperature is 230°C.

[0039] Comparative Example 1 is different from Example 1 in that no compound modified base liquid is used, only traditional PVB resin and plasticizer are used, the extrusion temperature is 140°C, the extrusion rate is 1500kg / h, and the mold temperature is 200°C.

[0040] Comparative Example 2 is different from Example 1 in that only new ester oil is used without adding silane coupling agent, the extrusion temperature is 145°C, the extrusion rate is 1600kg / h, and the mold temperature is 210°C.

[0041] Comparative Example 3 is different from Example 1 in that only silane coupling agent is used without adding new ester oil, the extrusion temperature is 150°C, the extrusion rate is 1700kg / h, and the mold temperature is 220°C.

[0042] In order to ensure that the various performance indicators of the PVB interlayer prepared in the above examples meet the requirements, detailed testing items were carried out. The following is a detailed testing method for each testing item.

[0043] 1. Wedge shape detection

[0044] Wedge shape is an important indicator for evaluating whether the PVB interlayer meets the design requirements. The method for testing wedge shape is as follows:

[0045] Detection method: Use an offline contact thickness gauge to measure the thickness of the diaphragm section by section, and then calculate the wedge value of each point through an integral algorithm.

[0046] Testing steps:

[0047] Sample preparation: Cut the PVB interlayer sample to be tested into appropriate size, and ensure that its surface is flat, free of bubbles and wrinkles. Thickness gauge calibration: Before measuring, calibrate the offline contact thickness gauge to ensure measurement accuracy.

[0048] Thickness measurement: Fix the diaphragm on the measuring platform and use an offline contact thickness gauge to measure the thickness of the diaphragm section by section. The measurement should cover the entire diaphragm surface and record the thickness data of each measuring point.

[0049] Data processing: Input the measured thickness data into the computer and use the integral algorithm to calculate the wedge value of each point.

[0050] Result analysis: Analyze the calculation results to ensure that the wedge degree is within the design range (0.2-0.8mrad). For samples that do not meet the requirements, adjustments and retests are required.

[0051] 2. Melt index detection

[0052] Melt index is an important indicator for evaluating the processing performance of PVB interlayer at high temperature. The test method is as follows:

[0053] Testing method: Use a melt index meter to measure the melt flowability of the PVB interlayer. Testing steps:

[0054] Sample preparation: Cut the PVB interlayer sample into small pieces and weigh a certain amount (usually 2-5 grams). Instrument preheating: Preheat the melt indexer to the set temperature (usually 140°C) and wait for the temperature to stabilize. Sample loading: Place the sample into the heating cylinder of the melt indexer and use the piston to press the sample.

[0055] Measurement process: Set the test time (usually 10 minutes) and record the mass of the molten material passing through the standard die within a certain period of time.

[0056] Result calculation: Calculate the melt index (g / 10min) of the sample and record the result. Generally, the melt index is required to be between 2-5g / 10min.

[0057] 3. Dynamic Mechanical Analysis (DMA)

[0058] DMA is used to evaluate the storage modulus and loss modulus of PVB interlayer to understand its mechanical properties.

[0059] The detection method is as follows:

[0060] Testing method: Use dynamic mechanical analyzer for testing. Testing steps:

[0061] Sample preparation: Cut the PVB interlayer film sample to an appropriate size (usually 10mmx50mm) and ensure that the sample surface is flat.

[0062] Instrument calibration: Before testing, DMA instruments are calibrated to ensure measurement accuracy. Sample installation: The sample is fixed in the fixture of the DMA instrument to ensure its stability.

[0063] Test setup: Set the test frequency (usually 1Hz) and temperature range (usually -50℃ to 150℃). Measurement process: Start the DMA instrument and record the storage modulus and loss modulus of the sample at different temperatures and frequencies. Data analysis: Analyze the test results and evaluate the mechanical properties of the sample.

[0064] 4. Differential Scanning Calorimetry (DSC)

[0065] DSC is used to detect the glass transition temperature and melting peak temperature of PVB interlayer to evaluate its thermal stability. The detection method is as follows:

[0066] Detection method: Use differential scanning calorimeter for testing. Detection steps:

[0067] Sample preparation: Weigh a certain amount of PVB interlayer sample (usually 5-10 mg) and place it in the DSC sample tank. Instrument calibration: Before testing, calibrate the DSC instrument to ensure measurement accuracy.

[0068] Test setup: Set the temperature scan range (usually 20°C to 200°C) and the heating rate (usually 10°C / min).

[0069] Measurement process: Start the DSC instrument, record the heat flow changes of the sample, and calculate the glass transition temperature and melting peak temperature. Data analysis: Analyze the test results and evaluate the thermal stability of the sample.

[0070] 5. Transmittance and haze detection

[0071] Transmittance and haze are important indicators for evaluating the optical properties of PVB interlayer. The test method is as follows: Test method: Use a transmittance and haze meter for testing.

[0072] Testing steps:

[0073] Sample preparation: Cut the PVB interlayer film sample to an appropriate size (usually 10cmx10cm) and ensure that there is no dirt on the sample surface.

[0074] Instrument calibration: Before testing, calibrate the transmittance and haze meters to ensure measurement accuracy.

[0075] Sample installation: Fix the sample on the test table of the transmittance and haze meter.

[0076] Test setup: Adjust the positions of the light source and detector to ensure that the light passes perpendicularly through the sample.

[0077] Measurement process: Start the instrument, record the intensity of transmitted light, and calculate the transmittance (%) and haze (%). Result analysis: Analyze the test results, the transmittance is generally between 89-90%, and the haze is between 0.2-0.4%.

[0078] 6. Adhesion (PUMMEL test)

[0079] The PUMMEL test is used to evaluate the adhesion between the PVB interlayer and the glass. The test method is as follows: Test method: Use the PUMMEL tester to perform the peel test.

[0080] Testing steps:

[0081] Sample preparation: Pre-bond the PVB interlayer to the glass sample and cut it into appropriate size.

[0082] Curing treatment: The pre-bonded sample is cured under set temperature and humidity conditions, usually at 70°C and 50% relative humidity for 24 hours.

[0083] Sample installation: Install the cured sample on the PUMMEL tester.

[0084] Test setup: Set the test parameters, such as peel speed (usually 100 mm / min).

[0085] Measurement process: Start the PUMMEL tester, perform a peel test on the sample, and record the adhesion (N / cm). Result analysis: Analyze the test results, the adhesion is generally between 4-7.

[0086] 7. Anti-penetration performance test

[0087] The penetration resistance is used to evaluate the safety of PVB interlayer. The test method is as follows:

[0088] Testing method: Use a drop ball tester for testing. Testing steps:

[0089] Sample preparation: Cut the PVB interlayer sample to the appropriate size and ensure the surface is flat. Sample installation: Fix the sample on the test platform.

[0090] Test setup: Set the drop height (such as 4 meters or 6 meters) and use a standard steel ball. Measurement process: Release the steel ball from the set height to simulate the impact.

[0091] Result record: record the damage of the sample and evaluate the anti-penetration performance.

[0092] Result analysis: Analyzing the test results, the anti-penetration performance is generally above 4 meters.

[0093] 8. Optical distortion change detection

[0094] The change in optical distortion is used to evaluate the optical performance of PVB interlayer in actual use. The detection method is as follows:

[0095] Detection method: Use optical detection equipment for testing.

[0096] Testing steps:

[0097] Sample preparation: Cut the PVB interlayer film sample into appropriate size and ensure the surface is flat.

[0098] Instrument calibration: Before testing, calibrate the optical testing instrument to ensure measurement accuracy. Sample installation: Fix the sample on the testing platform.

[0099] Test setup: Adjust the positions of the light source and detector to ensure that the light passes perpendicularly through the sample.

[0100] Measurement process: Start the optical detection instrument and record the deviation of the light after passing through the sample. Result analysis: Calculate the change in optical distortion and ensure that it is generally between 0.5'-2'.

[0101] 9. Ghosting amount detection

[0102] The ghosting amount is an important indicator for evaluating the ability of PVB interlayer to reduce image ghosting in practical applications. The detection method is as follows: Detection method: Use a ghosting detector for testing.

[0103] Testing steps:

[0104] Sample preparation: Cut the PVB interlayer sample to the appropriate size and ensure that the surface is flat and free of dirt. Instrument calibration: Before testing, calibrate the ghost detector to ensure measurement accuracy.

[0105] Sample installation: Fix the sample on the detection platform to ensure its stable position.

[0106] Test setup: Adjust the light source and imaging system to ensure that the light passes perpendicularly through the sample.

[0107] Measurement process: Start the ghosting detector and record the clarity and ghosting amount of the image after the sample passes. Result analysis: Analyze the test results to ensure that the ghosting amount is within the design range.

[0108] The following data were obtained by measuring multiple examples and comparative examples according to the above measurement method.

[0109] Table 1 Specific test data of the embodiments and comparative examples

[0110]

[0111]

[0112] By comparing the detection parameters of each embodiment with the comparative example, the tabular data shows that the embodiment using the compound modified base oil performs well in achieving the wedge target value. For example, the wedge 1 and wedge 2 test values ​​of Example 1 are 0.31 mrad and 0.62 mrad, respectively, which are highly consistent with the target values. The test values ​​of the comparative example are obviously deviated from the target value. For example, the wedge 1 and wedge 2 test values ​​of comparative example 1 are 0.12 mrad and 0.33 mrad, respectively. This shows that the compound modified base oil can effectively control the wedge angle of the diaphragm, ensure the accuracy of the multi-angle design, and help improve the display effect of the HUD and ADAS systems at different viewing angles.

[0113] Optical ghosting

[0114] Optical ghosting is one of the important indicators for measuring the optical performance of the film. The table data shows that the optical ghosting 1 and ghosting 2 of the embodiment are lower than those of the comparative example. For example, the optical ghosting 1 and ghosting 2 of Example 3 are 0.3Δ and 0.4Δ respectively, while the corresponding values ​​of comparative example 2 are 1.1Δ and 1.2Δ. This shows that the compound modified base oil can significantly reduce optical ghosting and improve the display effect of HUD and ADAS systems. Transmittance and haze

[0115] The light transmittance and haze of the embodiments are both kept within a good range, with the light transmittance between 89.0% and 89.5% and the haze being 0.3%, while the light transmittance of the comparative examples is lower and the haze is higher. For example, the light transmittance of Example 2 is 89.2% and the haze is 0.3%, while the light transmittance of Comparative Example 2 is 87.5% and the haze is 0.6%. This shows that the compound modified base oil can significantly improve the light transmittance of the film and reduce the haze, making it more excellent in optical properties.

[0116] Adhesion and penetration resistance

[0117] The data in the table show that the PUMMEL test results of the bonding force of the embodiments are all between 5 and 6, and the penetration resistance is between 5 and 6 meters, while the bonding force and penetration resistance of the comparative examples are poor. For example, the bonding force of Example 4 is 6, and the penetration resistance is 6 meters, while the bonding force of Comparative Example 3 is 2, and the penetration resistance is 2 meters. This shows that the diaphragm using the compound modified base oil performs better in mechanical properties and can provide higher safety.

[0118] DMA and DSC testing

[0119] In the DMA test, the glass transition temperature of the embodiments is higher than that of the comparative examples. For example, the glass transition temperature of Example 3 is 33°C, while that of Comparative Example 2 is 27°C. In the DSC test, the melting peak temperature of the embodiments is also higher than that of the comparative examples. For example, the melting peak temperature of Example 5 is 169°C, while that of Comparative Example 3 is 157°C. This shows that the compound modified base oil also has significant advantages in improving the thermal properties of the diaphragm.

[0120] Through the analysis of the test data, it can be seen that the compound modified base oil has significant advantages in the manufacturing process of multi-angle wedge-shaped PVB interlayer. Specifically:

[0121] Processing convenience: The use of compound modified base oil makes it easier to achieve the target value of diaphragm wedge shape in actual production, ensuring the accuracy of multi-angle design.

[0122] Improved optical performance: The film using compound modified base oil has excellent performance in optical ghosting, transmittance and haze, which significantly improves the display effect of HUD and ADAS systems.

[0123] Enhanced mechanical properties: The application of compound modified base oil significantly improves the adhesion and penetration resistance of the diaphragm, and enhances the durability and safety of the diaphragm.

[0124] Improved thermal properties: The compounded modified base oil also performs well in improving the glass transition temperature and melting peak temperature of the diaphragm, further enhancing the overall performance of the diaphragm.

[0125] In summary, the application of compound modified base oil not only improves the optical and mechanical properties of multi-angle wedge-shaped PVB interlayer, but also significantly improves the consistency of the production process and the accuracy of target value achievement, providing a solid foundation for the development of HUD and ADAS systems.

[0126] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the technical principles of the present invention, and these improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A method for manufacturing a multi-angle wedge-shaped PVB interlayer, characterized in that: The following steps are included Step 1, preparing a mixture of PVB resin and plasticizer; Step 2, synthesizing a composite modified base liquid; Step 3, adding the compounded modified base liquid to the PVB mixture; Step 4: Extrusion molding is performed using a high-efficiency extruder, and the extrusion temperature is controlled at 120-160°C; molding is performed using a high-precision wedge-shaped mold, and the wedge degree is controlled at 0.2-0.8mrad; and cooling and solidification are performed using an efficient cooling system.

2. The method for manufacturing a multi-angle wedge-shaped PVB interlayer according to claim 1, characterized in that: The compound modified base liquid comprises a novel ester oil and a composite novel silane coupling agent.

3. The method for manufacturing a multi-angle wedge-shaped PVB interlayer according to claim 2, characterized in that: The proportion of the composite novel silane coupling agent in the composite modified base liquid is in the range of 2-5%, and the rest is novel ester oil.

4. The method for manufacturing a multi-angle wedge-shaped PVB interlayer according to claim 2, characterized in that: The novel ester oil is synthesized by esterification reaction of glycerol and adipic acid under the action of p-toluenesulfonic acid catalyst.

5. The method for manufacturing a multi-angle wedge-shaped PVB interlayer according to claim 4, characterized in that: The novel composite silane coupling agent is synthesized by trichlorosilane and triethoxysilane under the action of a platinum catalyst.

6. The method for manufacturing a multi-angle wedge-shaped PVB interlayer according to claim 1, characterized in that: In the mixture of PVB resin and plasticizer, the proportion of PVB resin is 78-80%, and the proportion of plasticizer is 17-19%.

7. The method for manufacturing a multi-angle wedge-shaped PVB interlayer according to claim 2, characterized in that: The novel ester oil and the composite novel silane coupling agent are both neutralized by sodium hydroxide solution and refined by reduced pressure distillation.

Citation Information

Patent Citations

  • Preparation method of photovoltaic high-thermal-conductivity insulating PVB intermediate film

    CN110938269A

  • Preparation method of heat-insulation and sound-insulation glass interlayer material

    CN111647222A

  • Manufacturing method of variable-angle HUD visual enhanced PVB intermediate film

    CN117754839A

Cited By

  • Wedge-shaped polyvinyl butyral intermediate film as well as preparation method and application thereof

    CN122587256A